The fate of research abstracts submitted to a national surgical conference: a cross-sectional study to assess scientific impact - de Meijer, Vincent E.; Knops, Simon P.; van Dongen, Joris A.; Eyck, Ben M.; Vles, Wouter J. (The American journal of surgery, 2016)
Conference abstracts often lack rigorous peer review, but potentially influence clinical thinking and practice. To evaluate the quality of abstracts submitted to a large surgical conference, presentation and publication rates were investigated to assess scientific impact. A Cross-sectional study of abstracts submitted to Dutch Surgical Society meetings from 2007 to 2012 was conducted. Presentation rates, publication rates in MEDLINE-indexed journals using PubMed Central database, and actuarial times to subsequent publication were investigated. Of 2,174 submitted abstracts, 1,305 (60%) abstracts were accepted for presentation. Actuarial 1, 3, and 5-year publication rates were 22.4%, 62.2%, and 68.6% for presented abstracts, compared with 20.9%, 50.3%, and 57.7% for rejected abstracts, respectively (log-rank x2 23.728, df1, P < .001). Publications resulting from abstracts presented at the conference had a significantly higher mean (±standard error) impact factor (4.4 ± .2 vs 3.4 ± .1, P < .001), compared with publications from previously rejected abstracts. We advocate critical appraisal of the use of findings of scientific abstracts and conference presentations. The 5-year abstract-to-publication ratio is proposed as a novel quality indicator to allow objective comparison between scientific meetings. •Abstract presentation and publication rates were investigated to assess impact.•Two thirds of 2,174 submitted abstracts went on to full publication.•Presented research was published more timely and in journals with higher impact.•Scientific abstracts and conference presentations need critical appraisal.•The 5-year abstract-to-publication ratio is proposed as novel quality indicator.